The lady Eve - Sturges, Preston; Stanwyck, Barbara, 1907-1990; Fonda, Henry, 1905-1982; Coburn, Charles; Criterion Collection (Firm) ([New York, NY] : The Criterion Collection, 2020)
Barbara Stanwyck sizzles, Henry Fonda bumbles, and Preston Sturges runs riot in one of the all-time great screwballs, a pitch-perfect blend of comic zing and swoon worthy romance that Sturges wrote, directed, and produced.
DVD, full screen (1.3&:1); mono.
Title from sell sheet.
Barbara Stanwyck, Henry Fonda, Charles Coburn.
Originally released as a motion picture in 1941.
Rating: Not rated.
Special features: Audio commentary form 2001 with Marian Keane; Introduction from 2001 by Peter Bogdonavich; Interview from 2020 with Tom Sturges and friends; new video essay by David Cairns; Costume designs by Edith Head; Lux Radio Theatre adaptation of the film from 1942; audio recording of "Up the Amazon"; essay by Geoffrey O'Brien and a 1946 profile of Surges from Life Magazine.
Keywords: Man-woman relationships -- Drama; Swindlers and swindling -- Drama; Impostors and imposture -- Drama; Impostors and imposture; Man-woman relationships; Swindlers and swindling; Comedy films; Drama; Feature films; Comedy films; Feature films